The Influence of School Culture and Work Motivation on School Quality in Vocational Schools - Anwar, Khoirul; Rahman, Azhariah; Nurwahidin, Muhammad; Sutrisno, Sutrisno; Saputra, Nanda (Pascasarjana Universitas KH. Abdul Chalim, 2023)
This article describes the influence of school culture and work motivation on school quality at SMKN 1 Pungging Mojokerto. This article has used quantitative research with a descriptive approach. The population in this study were all teachers at SMKN 1 Pungging Mojokerto, totaling 111, while the people used 87 respondents. The results showed that 1. School culture significantly influences school quality with a significance value of t of 0.00. 2. Work motivation significantly affects school quality with a significance value of t of 0.000. 3. Simultaneously, school culture and work motivation significantly influence school quality with a calculated F value of 32.876 with an F significance value of 0.000 and a regression coefficient R2 of 43.9%.